IDENTIFICATION OF PHRASEOLOGICAL UNITS IN DISCOURSE (Journal of Universal Science Research, 2023)
PUs are known as complicated language units with endlessly varied manifestations in discourse. This calls for a systematic view of their actual use to gain a better insight into the discoursal dimension of text. The identification process needs, first and foremost, a profound understanding of the base form as an element of the system of language and its realization in discourse in either its core use or its instantial  use.